The unstoppable Wasp. Vol. 1, Unstoppable! - Whitley, Jeremy (Marvel Worldwide, Inc., 2017)
Nadia spent the entire first half of her life a captive of The Red Room, but now this teenage super scientist is on her own for the first time, and she's ready to spread her wings! Hank Pym's daughter has a lot of time to make up for and she's determined to change the world. You know, if she can get her U.S. citizenship first. Collecting: The Unstoppable Wasp 1-6.